Does Medicare‐eligible high‐risk breast cancer screening MRI target the right women?. Issue 2 (9th February 2020) - Lo, Glen; McLaughlin, Aden; Jacques, Angela; Dhillon, Ravinder; Porter, Gareth; Jayaratne, Thilina; Bose, Sharmistha; Bourke, Anita
Abstract: Introduction: MRI is the most sensitive modality to screen for breast cancer, but it is expensive with somewhat limited access. Audit of screening performance should reflect appropriate population targeting. Methods: An observational study on consecutively screened high‐risk women, assessment of the contralateral breast staging a new cancer, or surveillance in women with prior breast cancer or high‐risk lesion in Perth, Western Australia. All breast MRI studies from 1 January 2015 to 7 September 2018 were included. Studies were 3T comprising T2, DWI, ADC and T1‐weighted +/‐ fat saturation +/‐ IV gadolinium, +/‐ subtraction. DCE was read on the dynamics or DynaCAD (Invivo, Gainesville, FL, USA). Fellowship‐trained breast radiologists blindly double‐read by consensus; additional reader/s arbitrated. The reference standard was the histopathology result or cancer registry notification for cancer diagnoses and benign biopsies, benign follow‐up imaging or subsequent screening MRI. Results: Of 993 MRI studies in 554 women, 870 eligible MRI were performed in 471 women, and 706 had a reference standard. Median age was 44 years (range 18–80). The majority of studies (65% 457/706) were screening Medicare rebate‐eligible high familial risk; 26% for surveillance after a breast cancer or contralateral staging; 6% screened BRCA carriers. Eleven cancers were diagnosed, eight were MRI‐detected. Only two of these were at high‐risk screening MRI. Five were detected at staging contralateral ILC, after negative 2D mammography and ultrasound. Cancer prevalence was highest for staging contralateral ILC, at 600/10, 000 MRI, for high‐risk screening 77/10, 000 MRI and surveillance 116/10, 000 MRI. Conclusions: Cancers were predominantly detected in women undergoing preoperative staging of new invasive lobular carcinoma in the contralateral breast, rather than the Medicare rebate‐eligible high‐risk screening group.